Ritual Maddoja Bine dalam Praktik Pertanian Padi: Studi Etnografi - Natasya, Natasya; Jers, La Ode Topo (JURNAL KABANTI: Kerabat Antropologi, 2024)
This study is entitled "Maddoja Bine Ritual: Local Tradition of Bugis People in the Rice Farming System of Mondoke Village, Lambandia District, East Kolaka Regency". This study aims to describe and explain the Maddoja Bine ritual procession and to find out the reasons why the Maddoja Bine ritual is still maintained and in the community of Mondoke Village, Lambandia District, East Kolaka Regency. This study uses the theory of cultural ecology by Julian H Steward using an ethnographic approach. The results of the study can be concluded that the maddoja bine ritual is a ritual carried out before spreading rice seeds in the fields and is closely related to the process of farming rice in the fields. The maddoja bine process includes mappamula ase, deliberation (tudang sipulung) determining the day, preparing ritual dishes, ma'baca-baca, manre sipulung and mattabela. In its implementation, the maddoja bine ritual has undergone changes due to the influence of agricultural technology, but the reason the maddoja bine ritual is still carried out today is to maintain the traditions passed down by previous generations and to honor Sangiang Serri with the hope of being given protection when carrying out the rice planting process, being given good results, abundant when harvesting and an expression of gratitude for the harvest process.